1998
DOI: 10.1093/emboj/17.21.6168
|View full text |Cite
|
Sign up to set email alerts
|

A novel direct interaction of endoplasmic reticulum with microtubules

Abstract: This paper is dedicated to the memory of Thomas KreisThe positioning and dynamics of organelles in eukaryotic cells critically depend on membrane-cytoskeleton interactions. Motor proteins play an important role in the directed movement of organelle membranes along microtubules, but the basic mechanism by which membranes stably interact with the microtubule cytoskeleton is largely unknown. Here we report that p63, an integral membrane protein of the reticular subdomain of the rough endoplasmic reticulum (ER), b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
211
2
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(228 citation statements)
references
References 58 publications
(67 reference statements)
14
211
2
1
Order By: Relevance
“…7). In HeLa cells, one band of 63 kDa was revealed with both the monoclonal and polyclonal antibody directed against p63 as reported previously (37,38). However, when immunoprecipitation was performed on HeLa cells expressing fulllength tau or the GFP alone, no p63 was detected in either tau or GFP immunoprecipitate.…”
Section: Fig 5 the Interaction Of Map2c And P63 In An Overlay Assaysupporting
confidence: 77%
See 1 more Smart Citation
“…7). In HeLa cells, one band of 63 kDa was revealed with both the monoclonal and polyclonal antibody directed against p63 as reported previously (37,38). However, when immunoprecipitation was performed on HeLa cells expressing fulllength tau or the GFP alone, no p63 was detected in either tau or GFP immunoprecipitate.…”
Section: Fig 5 the Interaction Of Map2c And P63 In An Overlay Assaysupporting
confidence: 77%
“…Here we report a novel association of MAP2 with RER membranes using subcellular fractionation, electron microscopy immunocytochemistry, and electron microscopy in an in vitro reconstitution assay. Moreover, we showed that this association involves the interaction of the MAP2 projection domain with a 63-kDa nonglycosylated type II integral RER membrane protein, termed p63, that was found to mediate the interaction between RER membranes and microtubules in a previous study (37)(38)(39). Taken together, our results suggest that the interaction between MAP2 and p63 might contribute to the preferential distribution of RER membranes in the dendritic processes.…”
supporting
confidence: 69%
“…7 and 8), which was very reminiscent of the ER rearrangement in COS-7 cells induced by overexpression of the cytoskeleton-binding membrane protein CLIMP-63 (58,59). In the case of CLIMP-63, this ER rearrangement is a direct consequence of the interactions between the cytoplasmic domain of CLIMP-63 with microtubules along the altered ER membranes (58). The reason why ADAM12 was able to induce a similar ER rearrangement is not clear, and the possibility that ADAM12 may interact with microtubules needs to be explored.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in mammals, CLIMP63 (cytoskeletal linking membrane protein p63) is required to interact with microtubules to stabilize the cortical ER network (see review in Vedrenne and Hauri [2006] and references therein; Klopfenstein et al, 1998). Growth of tubules in animal systems is also dependent on integral ER membrane proteins (e.g., stromal interaction molecule 1) that bind the plus end of growing microtubules (Grigoriev et al, 2008).…”
Section: Three-way Junction and Anchor Sites Are Stabilization Factormentioning
confidence: 99%